Why Psychotropic Drugs Don't Cure Mental Illness—But Should They? - Ivanov, Iliyan; Schwartz, Jeffrey M. (Frontiers in Psychiatry, 2021)
While pharmacological treatments for psychiatric disorders have offered great promise and have provided clinically meaningful symptom relief these treatments have had less effect on altering the course of these disorders. Research has provided many new insights about the effects of different psychotropic agents on the functions of various brain systems as investigators have embraced the “translational research model”. However, this theoretical approach of deconstructing complex behaviors into smaller measurable behavioral units and targeting brain systems that are hypothesized to underlie these discrete behaviors has offered little of practical clinical relevance to significantly improve the treatment of psychiatric disorders in this century. Radical new treatments have not emerged, and available treatments continue to provide symptom relief without resolution of the underlying conditions. Recent publications on the subject have attempted to identify the barriers to progress and have pointed out some of the limitations of the translational approach. It is our position that, given the present limitations of our therapeutic arsenal, both researchers and clinicians would be well-advised to pay closer attention to human specific factors such as the role of language, the creation of personal narratives, and how factors such as these interface with underlying biological diatheses in mental illness. These interactions between pathophysiology and intrapersonal processes may be critical to both the in vivo expression of the underlying biological mechanisms of psychiatric disease states, and to the development of enhancements in therapeutic efficacy. Lastly, we discuss the implications of more coherently integrating neuroscientific research and clinical practice for more effectively addressing the challenges of understanding and treating mental illness.